2024
DOI: 10.24084/repqj12.274
|View full text |Cite
|
Sign up to set email alerts
|

Power Stabilization System with Unique Pumped Storage to Stabilize Momentarily Fluctuating Power from Renewable Resources (Counter-Rotating Type Pump-Turbine Unit Operated at Turbine Mode)

Abstract: Abstract. This serial research proposes the hybrid power stabilization system with the counter-rotating type pump-turbine unit, to stabilize momentarily fluctuating power from renewable energy resources. In this paper, the experiments are verified that this type pump-turbine unit is reasonably effective to stabilize momentarily/instantaneously the unstably fluctuating power from renewable energy resources. Furthermore, an optimization for improving the hydrodynamic performance at turbine mode of this pump-turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[1][2][3][4] Thus far, many kinds of studies have been conducted on counter-rotating type pump-turbines to understand the mechanisms, internal flow characteristics, and hydrodynamic performance characteristics. [5][6][7][8][9] Kim et al 6,7 enhanced the turbine efficiency of a counter-rotating type pump-turbine unit being operated in turbine mode using various optimization techniques. The results showed that the turbine efficiency was improved by 2.68% at the best efficiency point as compared with the reference design.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Thus far, many kinds of studies have been conducted on counter-rotating type pump-turbines to understand the mechanisms, internal flow characteristics, and hydrodynamic performance characteristics. [5][6][7][8][9] Kim et al 6,7 enhanced the turbine efficiency of a counter-rotating type pump-turbine unit being operated in turbine mode using various optimization techniques. The results showed that the turbine efficiency was improved by 2.68% at the best efficiency point as compared with the reference design.…”
Section: Introductionmentioning
confidence: 99%
“…The reference counterrotating type pump-turbine unit was considered for this validation. Figure 5 shows the performance curve validation results for the turbine output and efficiency of the pump-turbine unit operated at turbine mode [10]. As shown in Figure 5, the numerical results are in good agreement with experimental data across the entire volume flow range.…”
Section: Resultsmentioning
confidence: 53%